The experience of breastfeeding in women's perspective: contributions to nursing - Laís Antunes Wilhelm; Carolina Carbonell Demori; Camila Neumaier Alves; Camila Nunes Barreto; Luiza Cremonese; Lúcia Beatriz Ressel (Universidade Federal de Santa Maria, 2015)
Aim: to know the experience of women about breastfeeding. Method: qualitative descriptive research. The participants were eleven women, randomly invited from the users of a basic health center. The data collection was made through semistructured interviews and the analytical procedure was thematic analysis. The research followed the 196/96 resolution and was approved by the Research Ethics Committee under number 0165.0.243.000-11. Results: the categories that emerged Popular and scientific knowledge regarding breastfeeding of women who have experienced and Family influences in the construction of knowledge in breastfeeding process. Conclusion: the interviewed women believe in the protective effect of breastfeeding and that it should be exclusively offered until the child is six month old. Moreover, they feel influenced by cultural aspects, reporting the relevance of the opinion of family and health professionals